2008
DOI: 10.1007/s00792-008-0162-x
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic diversity in one of the largest hypersaline coastal lagoons in the world

Abstract: Araruama Lagoon is an environment characterized by high salt concentrations. The low raining and high evaporation rates in this region favored the development of many salty ponds around the lagoon. In order to reveal the microbial composition of this system, we performed a 16S rRNA gene survey. Among archaea, most clones were related to uncultured environmental Euryarchaeota. In lagoon water, we found some clones related to Methanomicrobia and Methanothermococcus groups, while in the saline pond water members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 46 publications
0
31
0
10
Order By: Relevance
“…Interestingly, the lagoon water and the surrounding saline pond water harbour different Archaea and Bacteria groups. Moreover, culture-independent methods revealed a significant number of clones related to uncultured Archaea and Bacteria suggesting that the Araruama lagoon contain novel micro-organisms, distinct from those observed in other similar hypersaline environments (Clementino et al 2008).…”
Section: Other Relevant Areasmentioning
confidence: 99%
“…Interestingly, the lagoon water and the surrounding saline pond water harbour different Archaea and Bacteria groups. Moreover, culture-independent methods revealed a significant number of clones related to uncultured Archaea and Bacteria suggesting that the Araruama lagoon contain novel micro-organisms, distinct from those observed in other similar hypersaline environments (Clementino et al 2008).…”
Section: Other Relevant Areasmentioning
confidence: 99%
“…As expected, the authors found a great dominance of halophilic euryarchaeotes in their samples and a small number of crenarchaeotes associated with lineages found in marine vents. Curiously, in one of the samples, the halophilic sequences formed a distinct clade, suggesting the presence of new, undescribed, organisms in these waters [39, 40]. …”
Section: Archaea In Aquatic Environmentsmentioning
confidence: 99%
“…Nuestros resultados sugieren que en la comunidad microbiana de los tres manantiales predominan más los organismos del dominio Bacteria que los del dominio Archaea, lo cual se ha reportado en ambientes con salinidad de hasta 16 % (p/v) (Dong, et al, 2006;Perreault, et al, 2007;Clementino, et al, 2008); por otra parte, Swan, et al (2010) encontraron que en ambientes moderadamente hipersalinos (5 % (p/v) los organismos del dominio Archaea eran más que los del dominio Bacteria. Con respecto a la predominancia de Bacteria sobre Archaea, se ha discutido la razón de que en un mismo ambiente se tienda a encontrar menor diversidad en Archaea que en Bacteria, pese a que las arqueas contribuyen en gran proporción al total de los filotipos procariotas presentes en la mayoría de los ambientes en los que se han estudiado organismos de ambos dominios (Aller & Kemp, 2008).…”
Section: Caracterización De La Composición De Las Comunidades Microbiunclassified